2008
DOI: 10.1002/ldr.869
|View full text |Cite
|
Sign up to set email alerts
|

Land‐use and cover changes (1988–2002) around budongo forest reserve, NW Uganda: implications for forest and woodland sustainability

Abstract: Land-use and cover changes around Budongo Forest Reserve (BFR) were analysed from multi-temporal LandSat images (1988 and 2002) and associated field-based studies in [2003][2004]. Three major land-use and cover classes: forest/woodland, sugarcane plantations and grassland/shifting-cultivation/settlements were clearly discriminated. The area under sugarcane cultivation increased over 17-fold, from 690 ha in 1988 to 12729 ha in 2002, with a concomitant loss of about 4680 ha (8Á2 per cent) of forest/woodland, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 35 publications
3
63
0
Order By: Relevance
“…Mwavu and Witkowski, (2008) also found that Budongo forest cover in Northern Uganda had decreased significantly as sugarcane plantations had increased between 1988 to 2002. They attributed these changes to agricultural expansion, increasing human population exacerbated by large influxes of refugees, conflicts of interest and political interference in the management of Budongo Forest and the unclear land tenure.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Mwavu and Witkowski, (2008) also found that Budongo forest cover in Northern Uganda had decreased significantly as sugarcane plantations had increased between 1988 to 2002. They attributed these changes to agricultural expansion, increasing human population exacerbated by large influxes of refugees, conflicts of interest and political interference in the management of Budongo Forest and the unclear land tenure.…”
Section: Resultsmentioning
confidence: 90%
“…As humans try to meet their daily needs, they are subjecting forests, woodlands and grasslands to the highest rates of change (Pomeroy & Tushabe, 2004;MEA, 2005) resulting in land use/cover changes (Mwavu and Witkowski, 2008;Egeru and Majaliwa, 2009). While it is possible to identify with some certainty the factors underlying tropical deforestation in a general sense, it is very difficult to pinpoint a uniform set of drivers/causes and their relative contributions that apply generally at a global or even regional level (MEA, 2005).…”
mentioning
confidence: 99%
“…The three interrelated elements that are essential to achieving food security in each community are food availability (sufficient quantities available for consumption), food access (adequate resources to obtain appropriate foods for a nutritious diet), and food utilization (a diet providing sufficient energy and essential nutrients [11,26]. Results of the present study reveal that the people in this commercial sugarcane growing region are food insecure, as they do not always have both the physical and economic access to sufficient food to meet their dietary needs for a productive and healthy life [13,26,27].…”
Section: Food Security Situation and Coping Strategies Among Householdsmentioning
confidence: 99%
“…The magnitude of the changes can be quite different depending on the anthropogenic influences in specific areas (Roques et al, 2001;Mwavu and Witkowski, 2008).…”
Section: Author(s) Agree That This Article Remains Permanently Open Amentioning
confidence: 99%